Extreme rainfall indices in Brazilian mountain regions and potentially induced hydrological hazards - Ávila Díaz, Álvaro Javier (2016)
In order to understand the rising number of flash floods and mass movements in the densely populated region of southeastern Brazil, this study analyzes the spatial and temporal changes in precipitation from 1978 to 2014. We focus on the sensitivity of mountainous regions, specifically the Rio de Janeiro (RJMR) and Santa Catarina (SCMR) regions. Daily rainfall observations are aggregated into annual and seasonal indices, and RClimdex is used to evaluate a suite of precipitation and extreme event indices. Results show positive annual and seasonal precipitation trends during all seasons except for the winter season in the RJMR. Diverse change points in their time series, spatial differences in the trends at individual stations, and trends associated with elevation suggest that despite the close proximity of these two regions, climate impacts are not uniform across all of southeastern Brazil. Climate mechanisms responsible for the observed precipitation trends are identified, but additional work is needed to isolate the causes. Statistically significant positive correlations are discovered between mass movements/flash floods events and annual maximum 1–day and 5–day consecutive precipitation, and these indices may be useful indicators of natural hazard events for this region.